Identity in the Shadow of a Giant : How the Rise of China is Changing Taiwan - Gartner, Scott Sigmund, 1963-; James, Patrick; Li, Yitan; Huang, Chin-Hao (Book collections on Project MUSE., 2021)
This co-authored book examines the implications of the global ascent of China on cross-Strait relations and the identity of Taiwan as a democratic state, offering insights into policies for peaceful relations and prosperity across the Taiwan Strait.